Compounding Tailored Veterinary Chewable Tablets Close to the Point-of-Care by Means of 3D Printing - Erica Sjöholm; Rathna Mathiyalagan; Xiaoju Wang; Niklas Sandler (MDPI AG, 2022)
Certain patient populations receive insufficient medicinal treatment due to a lack of commercially available products. The number of approved veterinary products is limited, making animals a patient population with suboptimal medicinal treatments available. To answer to this unmet need, compounding and off-label use of human-marketed products are practiced. Both of which have a significant risk of preparation errors. Hence, there is a dire demand to find and implement a more automated approach to the accurate, precise, and rapid production of veterinary dosage forms close to the point-of-care. This study aimed to assess the use of semi-solid extrusion-based 3D printing for the preparation of tailored doses of theophylline in the form of a chewable dosage form suitable for veterinary use. This study proved that semi-solid extrusion-based 3D printing could successfully be utilized to manufacture pet-friendly, chewable theophylline-loaded tablets. The prepared dosage forms showed a high correlation (R2 = 0.9973) between the designed size and obtained drug amount and met the USP and Ph. Eur. content uniformity criteria. Furthermore, the stability study showed the dosage form being stable and able to be used for up to three months after printing.